The Role of Education in Curbing Social Problems among the Youth; An Islamic Perspective - SALIM , Ssuna; ABDULLAH , Syahrul Faizaz (Asian Journal of Empirical Research, 2013)
Social problems involving the youth is a global challenge that has attracted and continues to attract the attention of everybody, irrespective of their faith, geographical location, level of development and status. Although this problem has reached an alarming situation, there are yet sufficient studies suggesting Islamic comprehensive measures in curbing them. The descriptive, analytical and synthetic approach will be adopted which is mainly interpretative in the form of textual commentary. The study will begin by defining what a social problem is as conceived by educationists, emphasizing the Islamic view. The study will then asses the intensity of the problem from selected sample studies so far carried out, critically looking at the approaches and solutions thus far suggested in curbing these problems. The discussion will finally present an assessment of the Islamic teaching based on the Quran and Sunnah of the Prophet (peace be upon him) how these social problems involving the youth should be remedied, critically putting more emphasis on the recommendation of contemporary Muslim scholars.